Stolen innocence : my story of growing up in a polygamous sect, becoming a teenage bride, and breaking free of Warren Jeffs - Wall, Elissa; Pulitzer, Lisa (New York, NY : William Morrow, 2008)
Elissa Wall details her life growing up in the polygamous Fundamentalist Latter Day Saints religious sect, being forced into an unwanted marriage at the age of 14, and her courage to testify against FLDS leader Warren Jeffs.--From publisher description.
Prologue -- Part 1: -- 1: New mother -- 2: Growing up and keeping sweet -- 3: Good priesthood children -- 4: In light and truth -- 5: Rise of Warren -- 6: Out of control -- 7: Reassignment -- 8: Preparing for Zion -- 9: Revelation is made -- 10: Celestial law -- 11: Word of the prophet -- 12: Man and wife -- 13: All alone -- Part 2: -- 14: Survival begins -- 15: Destruction is upon us -- 16: Death comes to short creek -- 17: False prophet -- 18: Refuge in Canada -- 19: Nowhere to run -- 20: Pair of headlights -- 21: Promise not to tell -- 22: Story like mine -- 23: Love at last -- 24: Choosing my future -- Part 3: -- 25: New beginnings -- 26: Coming forward -- 27: Captured -- 28: Facing Warren -- 29: Trial begins -- 30: End is in sight -- 31: I am free -- Epilogue -- Author's note -- Acknowledgments.
Includes bibliographical references.
Keywords: Wall, Elissa; Jeffs, Warren, -- 1955-; Fundamentalist Church of Jesus Christ of Latter Day Saints; Forced marriage -- United States; Abused wives -- United States -- Biography; Marriage -- Religious aspects -- Church of Jesus Christ of Latter-day Saints; Mormons -- United States -- Biography; Polygamy -- United States; Mormons -- United States -- Biography; Jeffs, Warren, -- 1955-; Jeffs, Warren, -- 1955-; Wall, Elissa; Fundamentalist Church of Jesus Christ of Latter Day Saints; Abused wives; Forced marriage; Marriage -- Religious aspects -- Church of Jesus Christ of Latter-Day Saints; Mormons; Polygamy; United States; Wall, Elissa; Fundamentalist Church of Jesus Christ of Latter Day Saints; Jeffs, Warren, -- 1955-; Mormons -- United States -- Biography; Abused women -- Biography; Wife abuse -- United States; Teenage marriage -- United States; Marriage -- Religious aspects -- Fundamentalist Church of Jesus Christ of Latter Day Saints; Nonfiction; Autobiographies; Biographies; Autobiographies